Adoptive Cell Therapies for Glioblastoma - Bielamowicz, Kevin J.; Khawja, Shumaila; Ahmed, Nabil (Frontiers in Oncology, 2013)
Glioblastoma (GBM) is the most common and most aggressive primary brain malignancy and, as it stands, is virtually incurable. With the current standard-of-care, maximum feasible surgical resection followed by radical radiotherapy and adjuvant temozolomide, survival rates are at a median of 14.6 months from diagnosis in molecularly unselected patients(1). Collectively, the current knowledge suggests that the continued tumor growth and survival is in part due to failure to mount an effective immune response. While this tolerance is subtended by the tumor being utterly “self”, it is to a great extent due to local and systemic immune compromise mediated by the tumor. Different cell modalities including lymphokine-activated killer (LAK) cells, natural killer (NK) cells, cytotoxic T lymphocytes (CTL), and transgenic chimeric antigen receptor (CAR)- or αβ T cell receptor (TCR) grafted T cells are being explored to recover and or redirect the specificity of the cellular arm of the immune system towards the tumor complex. Promising phase I/II trials of such modalities have shown early indications of potential efficacy while maintaining a favorable toxicity profile. Efficacy will need to be formally tested in phase II/III clinical trials. Given the high morbidity and mortality of GBM, it is imperative to further investigate and possibly integrate such novel cell-based therapies into the current standards-of-care and herein we collectively assess and critique the state-of-the-knowledge pertaining to these efforts.